2013
DOI: 10.1210/jc.2012-3516
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Islet Immunoreactivity by Adiponectin Is Attenuated in Human Type 1 Diabetes

Abstract: These data indicate that T cells are released from the antiinflammatory effects of adiponectin in T1D and suggest a mechanism linking insulin resistance and islet immunity. Furthermore, we suggest that interventions that reduce insulin resistance could modulate the inflammatory process in T1D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These findings suggest that the mechanisms for wound-healing abnormalities associated with TID could be related to loss of insulin actions in fibroblasts. Metabolic changes such as hyperglycemia can inhibit insulin actions in several tissues in T1D and T2D patients (40). This supportive evidence in fibroblasts from other studies demonstrated selective inhibition of insulin action in the IRS/PI3K/AKT cascade, without loss of activation of MAPK (41).…”
Section: Discussionsupporting
confidence: 77%
“…These findings suggest that the mechanisms for wound-healing abnormalities associated with TID could be related to loss of insulin actions in fibroblasts. Metabolic changes such as hyperglycemia can inhibit insulin actions in several tissues in T1D and T2D patients (40). This supportive evidence in fibroblasts from other studies demonstrated selective inhibition of insulin action in the IRS/PI3K/AKT cascade, without loss of activation of MAPK (41).…”
Section: Discussionsupporting
confidence: 77%
“…Switching the cytokine environment to an anti-inflammatory profile could potentially modulate the immune response that leads to beta cell destruction in type 1 diabetes. Work in our laboratory has also demonstrated that the expression of adiponectin receptors by peripheral blood immune cells is reduced in patients with type 1 diabetes [20]. This reduction in receptor expression releases effector T cells from the anti-inflammatory effects of adiponectin, resulting in a proinflammatory response to beta cell antigen.…”
Section: Search Strategymentioning
confidence: 86%
“…ADIPOR1 and ADIPOR2 are also abundantly expressed in the hypothalamus and cerebral vascular endothelial cells (Carson et al, 2013). Studies showed that adiponectin receptors are closely associated with diabetes (Pang et al, 2013), metabolic syndrome (Peters et al, 2013), and cardiovascular disease (Ding et al, 2012). They can affect cell metabolism and function and are one of the important mechanisms in the promotion and development of disease (Richards et al, 2012).…”
Section: Discussionmentioning
confidence: 99%